Sri Ulfa Rahayu HADIS: TAFSIR SOSIAL TERHADAP TEKS NORMATIF DI ASIA TENGGARA - Sri Ulfa Rahayu (Al-Mu'tabar, 2022)
The Qur'an and Hadith as the first and second sources of Islamic teachings, are very important to understand and practice. One of the teachings that have rules in the Qur'an and Hadith is about social behavior in Southeast Asia regarding halal bi halal and the tradition of meugang before Ramadan, whether in accordance with Islamic teachings or not. The purpose of this research is to find out the arguments about halal bi halal and meugang before Ramadan based on the Qur'an and Hadith. The method of this writing is qualitative with data collection through the existing literature, namely literature review. Furthermore, with a revelation and descriptive approach. The results obtained are halal bi halal in Islam known as shilaturrahim and has source. As for meugang, this is a tradition of sharing food, which in the Hadith there is a statement about sharing food and giving gifts.